2022
DOI: 10.1155/2022/9082455
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Genetic Variants Are Associated with Protection to Clinical Severity of COVID-19 among Patients from Rio de Janeiro, Brazil

Abstract: COVID-19 has a broad spectrum of clinical manifestations, from asymptomatic or mild/moderate symptoms to severe symptoms and death. The mechanisms underlying its clinical evolution are still unclear. Upon SARS-CoV-2 infection, host factors, such as the inflammasome system, are activated by the presence of the virus inside host cells. The search for COVID-19 risk factors is of relevance for clinical management. In this study, we investigated the impact of inflammasome single-nucleotide polymorphisms (SNPs) in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
(107 reference statements)
3
4
0
Order By: Relevance
“…Presence of the polymorphism results in a substitution of phenylalanine by isoleucine at position 102 in the classical transcript variant 1 of CARD8 gene (NM_001184900.3), although it could lead to a termination codon in other splicing variants of the gene (transcript variants 12, 14, and 17–19; , accessed on 12 July 2023). Similar to the study conducted by de Sá et al [ 41 ], in our cohort we observed a protective effect of CARD8 -rs2043211 polymorphism in COVID-19 severity ( Table 4 ); however, this finding was lost in multivariate analysis ( Table 5 ).…”
Section: Discussionsupporting
confidence: 90%
“…Presence of the polymorphism results in a substitution of phenylalanine by isoleucine at position 102 in the classical transcript variant 1 of CARD8 gene (NM_001184900.3), although it could lead to a termination codon in other splicing variants of the gene (transcript variants 12, 14, and 17–19; , accessed on 12 July 2023). Similar to the study conducted by de Sá et al [ 41 ], in our cohort we observed a protective effect of CARD8 -rs2043211 polymorphism in COVID-19 severity ( Table 4 ); however, this finding was lost in multivariate analysis ( Table 5 ).…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have shown that genetic variants of the NLPR3 inflammasome can influence the individual response to SARS-CoV-2 infection, which emphasizes that the activation of NLPR3 plays a key role during the inflammatory response. 29,30 Yet, this is the first time that the highly expressed circulating miRNA was proposed as a positive regulator of NLPR3 during COVID-19 due to the inhibition of the BCL6 repressor, and as a biomarker of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the pro-inflammatory effect of miR-205-5p by increasing NLPR3 expression, this miR has been previously implicated in antiangiogenic effects in diabetes-induced limb ulcer. 30 High levels of circulating miR-205-5p have been found to decrease protein levels of vascular endothelial growth factor A (VEGFA) through direct binding on its 3′UTR mRNA in “in vitro” and “in vivo” models. 31 VEGFA is one of the most important members of the VEGF family, 32 and its angiogenic activity is strongly induced by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the evident participation of the inflammasome in SARS-CoV-2 infection, it is plausible to think that inflammasome-related genes could provide new perspectives for illuminating the pathological processes potentially influencing the worsening and increased mortality of patients with this devastating disease. In fact, previous reports have suggested that the genetic variants related to the inflammasome are involved in the susceptibility or progression of COVID-19 disease [19][20][21][22][23][24][25]. However, our understanding of the complex interconnection between SARS-CoV-2 and inflammasome-related genes is still incomplete.…”
Section: Introductionmentioning
confidence: 99%